Coriolis-induced liquid breakup and spray evolution in a rotary slinger atomizer: Experiments and analysis. (February 2021) - Sahu, Srikrishna; Chakraborty, Arnab; Maurya, Dalton
Highlights: Liquid atomization in a rotary slinger atomizer is experimentally and analytically studied. The visualization images suggested strong influence of Coriolis force on the liquid delivery mode in the slinger orifices. A novel model was developed that accounts for the Coriolis and surface tension forces and explained the observations. Both thickness and span of the liquid flow in an orifice channel influence the liquid breakup modes/regimes. Correlations for the measured AMD and SMD were derived in terms of Coriolis Bond number and momentum flux ratio. Abstract: Understanding the physics of primary liquid breakup process and its correlation with the evolution of spray characteristics in a rotary slinger atomizer is the goal of the present research. Experiments were conducted in a high-speed slinger test rig that houses a static liquid delivery manifold to uniformly supply the liquid to the rotating slinger disc that contains a single row of orifices carved on its peripheral surface for liquid injection.The atomizer was operated for a wide range of conditions by varying the rotational speed and liquid feed rate. The liquid breakup structure at the exit of the slinger orifices was visualized using front light illumination technique, while the droplet size was measured at different radial stations away from the slinger surface by application of the Interferometric Laser Imaging for Droplet Sizing (ILIDS) technique. The visualization images highlighted strong influence of Coriolis force as the liquid tends to accumulate on one side of the channel (that is opposite to the rotational direction) for all cases. It was observed that while the liquid thickness is smaller for higher rotational speed, it does not vary much with liquid feed rate at the same speed and, instead, in such case the span of the liquid is wider. A theoretical analysis was developed to describe the in-channel liquid behaviour that accounts for the effect of Coriolis and surface tension forces. Interestingly, the theory could explain the above observations. The differences in the predictions in comparison to the analysis by Dahm et al. (2006a) was attributed to the assumption of annular film flow in the latter. The liquid breakup mode (stream, sheet or transition mode) could be described by Coriolis Bond number ( B o ) that refers to the ratio of Coriolis to surface tension forces and proportional to the spread parameter (span to thickness ratio), while the liquid breakup regimes were identified on a B o − q plot, where q is the liquid to air momentum flux ratio. The variation of characteristic droplet sizes with both rotational speed and feed rate were examined, and again some interesting trends are identified. The correlation between liquid breakup mode/regime with the measured droplet size was established using the above non-dimensional numbers.